The electrochemistry of metalloenzymes confined in ionic liquids - Wang, Y (2016)
Enzymes are superb catalysts with high selectivity and catalytic efficiency. Ionic liquids have negligible volatility, good electric conductivity, and high thermal and chemical stability, which are powerful electrolytes for electrochemical processes. To understand how to apply enzymatic catalysis in ionic liquids to carbon-neutral technologies, this thesis investigates the electrochemical properties of three metalloenzymes that are inspirational catalysts for fuel cells and CO2 reduction in an almost dry condition in ionic liquids, by protein film electrochemistry (PFE). Hydrogenase-1 from Escherichia coli (Hyd-1) catalyses H2 oxidation at turnover frequencies ca. 100 s–1. Bilirubin oxidase (BOD) is commercially available and catalyses the four-electron O2 reduction at a lower overpotential than Pt and at turnover frequencies ca. 100 s–1. Each enzyme was immobilized on a carbon electrode that contacts an aqueous microvolume (1-2 μL) surrounded by a hydrophobic ionic liquid. Separately, the enzymes display excellent electrocatalytic activity: brought together at a synaptic junction, an anode and cathode modified with each enzyme constitute a membrane-less fuel that produces over 0.8 V when equilibrated with 96 % H2-4 % O2. Carbon monoxide dehydrogenase from Carboxydothermus hydrogenoformans I (CODH ICh) shows considerable electrocatalytic activity in tiny aqueous shell confined by EMIMTFSI saturated with CO2. CO2 is exceptionally soluble in ionic liquids, which are practical for CO2 uptake, capture and storage. CO2 reduction and CO oxidation electrocatalysed by CODH ICh occurred at the same time in the tiny aqueous shell, according to cyclic voltammetry. Finally, a steady state was achieved.